BROADCASTING MANAGEMENT STRATEGY V RADIO 106.6 FM JAKARTA IN MAINTAINING POSITIONING AS A FEMALE RADIO - Radjagukguk, Djudjur Luciana; Wahidawati, Mega Mei (JILPR Journal Indonesia Law and Policy Review, 2020)
V Radio listeners have decreased significantly since 2018. Even female listeners have also experienced a decline since the beginning of 2020. Nielsen's data recorded in early 2020 the percentage of female listeners was only 33%, while the rest were male listeners. Of course this is inversely proportional to the V Radio segmentation which should be women. The research objective was to find out and analyze how V Radio broadcasting management to maintain its position as a female radio was implemented by the top ranks of the V Radio team. This research uses qualitative research methods with a descriptive approach. The author uses Stoner's broadcast management theory which consists of four elements, namely planning, organizing, directing / giving influence, and monitoring. And there is one more element, namely evaluation. The data sources used were Nielsen data sources and interviews with V Radio management and staff. The data analysis process was carried out by means of theoretical data analysis. The result of this research is that V Radio applies all broadcast management theory according to Stoner. In the planning stage V Radio uses short-term planning to long-term planning. Organizing V Radio using vertical and horizontal structures. Instructions and supervision on V Radio are carried out internally and externally. And the last is the evaluation stage which is carried out periodically. Evaluation is carried out every 6 months which is called the Key Performance Appraisal (KPA)